The Effort to Reduce Over Capacity in Correctional Facilities through Social Work Alternative Punishment - Maiza Putri (Faculty of Law, Universitas Lampung, 2021)
Overcapacity in prisons usually happens due to the high number of incoming inmates which is not directly proportional to the capacity of the correctional institution. It is a problem in realizing the aim of both the correctional system and the criminal justice system and raises the urgency of alternative penalties application. This research aims twofold: First, to uncover the causes of prison overcapacity, Second, to elaborate on how policy is being developed toward alternative punishment to reduce overcapacity. This study takes a normative and empirical legal approach, with data gathered through literature reviews and field studies. In conclusion, it would appear that alternative punishments are essential to change the negative views regarding the application of criminal sanctions in prison into the application of alternative criminal sanctions for social work that have a positive impact. The punishment that can be used as an alternative to imprisonment is the social work penalty. The social work penalty is considered to reduce the negative impact on the implementation of imprisonment in prisons that experience overcapacity. This research suggests that the social work criminal formulation policy should be immediately formulated in the Draft of Criminal Code (RUU KUHP).